Blunt Head Trauma and Headache - Chelse, Ana B. (Pediatr Neurol Briefs, 2015)
Investigators from New York Presbyterian Morgan Stanley Children's Hospital examined whether having an isolated headache following minor blunt head trauma was suggestive of traumatic brain injury (TBI) among a large cohort of children 2-18 years of age.